(3GdeMGSHI hGdMGSHGJ GdBdjIs - (3UdGM GdOjf YHO GdefYe(B, (3eHGQcs; (3eMeO GdHGHdj(B, s ((3GdEScfOQjI(B:s (3OGQ GdeWHhYGJ GdLGeYjI(B,s, 2008)
(3jVe echfGJ GdMGSH GdBdj , (BWindows XP (3, HQfGeL GcSd hJWHjbGJg GdMSGHjIs
Keywords: (3GdMGSH GdBdjs; (3GdeMGSHIs; (3GdeMGSHI GdBdjIs